Organizational endogenous development: the micro-foundations, opportunities and real options perspective - Krupski, Rafał; Piórkowska, Katarzyna; Sus, Aleksandra (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper presents significantly salient issues in the field of strategic management in terms of organizational endogenous development understood as the concept integrating three areas. Consequently, the research questions of the paper are as follows: (1) Is it possible to describe a strategy of contemporary organizations assuming their endogenous development? (2) What constitutes the fundamentals of organizational endogenous development? and (3) How do those fundamentals affect organizational endogenous development? Hence the aim of the paper is to enrich the strategic management field and consequently to present the elements of the triad: socio-psychological managerial characteristics (predictors, SMC) – opportunities (O) – real options (RO) in terms of strategic management and to endeavour by the means of that triad, to answer the research questions. The method that has been used is extensive literature review, therefore inference is deductive. The first section presents opportunities as potential determinants of organizational endogenous development. The real options concept constituting the support for implementing opportunities approach has been described in the second section. Then, socio-psychological managerial characteristics as the micro-foundations of organizational endogenous development have been emphasized and presented. Finally, the conclusion with final remarks, limitations, and research directions has been presented
Argumenta Oeconomica, 2017, Nr 1 (38), s. 63-97
Keywords: socio-psychological micro-foundations; opportunities; real options